More summertime low-power production extremes in Germany with a larger solar power share - Ho-Tran, Linh; Fiedler, Stephanie (Solar energy, 2024)
The share of renewable energy in Germany is increasing to meet the climate-neutral targets in 2050. Weather-driven anomalous in renewable power production thus can pose greater challenges in balancing electricity supply and demand. This study investigates the seasonal differences in extreme events in photovoltaic (PV) plus wind power production in Germany for installed capacities for the present and 2050. The results indicate an increase in such extreme events in the summer half-year, mostly pronounced in May. Extremely low production with a duration of 14 days in winter is associated with atmospheric blocking, with very low wind power production anomalies of up to −37%. Summertime extremely low production is associated with stationary cyclonic weather patterns, with similar reductions in both energy sources of up to −19%. Case studies illustrate the dependency of the benefits of cross-border electricity transmission lines on the prevailing wind direction. North-South transmission lines are beneficial when an anticyclone moved from the Northwest to Germany, whereas West-East transmission lines are beneficial when a cyclone moved from the Southwest to Germany. The results imply an increased risk of extremely low power production during future summers in Germany and suggest monitoring sequences of different weather patterns for the energy sector.
Online verfügbar 24 October 2024, Version des Artikels 24 October 2024
Gesehen am 07.04.2025